2023
DOI: 10.7196/samj.2023.v113i4.16772
|View full text |Cite
|
Sign up to set email alerts
|

Placental histopathology, maternal characteristics and neonatal outcome in cases of preterm birth in a high-risk population in South Africa

Abstract: Background. Preterm birth remains a global health concern and is one of the most common pregnancy complications associated with perinatal morbidity and mortality.Objective. To investigate placental pathology and its associations with obstetric, maternal and neonatal outcomes in the Eastern Cape region of South Africa (SA) in order to help understand its associations with preterm birth in that region. Methods. In this prospective study, placentas were collected consecutively fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This indicates that preterm placentas have fewer microbial constituents within their microbiome. However, the higher alpha diversity in term placentas compared to preterm placentas, and higher alpha diversity in placentas with chorioamnionitis compared to those without CAM (P=0.0061) correlates with the higher incidence of CAM in term placentas compared to preterm placentas (P=0.002) [27]. Prince et al also found that chorioamnionitis was associated with lower alpha diversity in the placental membrane microbiome, although associated with preterm birth in their study [6].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This indicates that preterm placentas have fewer microbial constituents within their microbiome. However, the higher alpha diversity in term placentas compared to preterm placentas, and higher alpha diversity in placentas with chorioamnionitis compared to those without CAM (P=0.0061) correlates with the higher incidence of CAM in term placentas compared to preterm placentas (P=0.002) [27]. Prince et al also found that chorioamnionitis was associated with lower alpha diversity in the placental membrane microbiome, although associated with preterm birth in their study [6].…”
Section: Discussionmentioning
confidence: 78%
“…All cases were evaluated histologically by a single pathologist using a standardized placental macroscopic evaluation protocol and histology template approved and validated by the NHLS laboratory. Prof CA Wright, anatomical pathologist, a specialist in placental histology, reviewed all the placenta specimens for this study and histopathology data was published in 2023 [27]. The pathologist was blinded to all information except gestational age and whether live-born or stillbirth.…”
Section: Placentasmentioning
confidence: 99%
See 1 more Smart Citation